PENDAMPINGAN PENGEMBANGAN ALAT PERAGA EDUKATIF DALAM PEMBELAJARAN MATEMATIKA BAGI GURU SEKOLAH DASAR DI DESA PELABUHAN DALAM KECAMATAN PEMULUTAN - Octarina, Sisca; Indrawati, Indrawati; Puspita, Fitri Maya; Bangun, Putra Bahtera Jaya; Yuliza, Evi (LPPM Universitas Bina Bangsa, 2024)
It is a fallacy to assume that mathematics can be taught in a one-way manner, whereby the teacher reads the material and students sit and listen. In order to facilitate comprehension of the material being taught, a variety of teaching aids are required. A further challenge is that not all teachers have the time to create their teaching aids. Furthermore, the creation of teaching aids necessitates a considerable degree of creativity. Not all educational institutions have the financial resources to procure instructional materials, particularly those in public schools in underprivileged regions. The objective of this activity is to assist in the development of educational teaching aids for teachers and educators in elementary schools in Pelabuhan Dalam Village, Pemulutan District, Ogan Ilir Regency, South Sumatra. This activity will enhance students' engagement and comprehension of the subject matter presented by the instructor. The mentoring activity is comprised of several stages, commencing with a survey, a presentation of material on the creation of teaching aids, tutorials on the construction of said aids, and concluding with the practical application of said aids by the activity participants. The activity was conducted over four meetings and ended with a post-test to assess the participants' comprehension of the mentoring material that had been provided. The participants in this service activity were 14 elementary school teachers and educators. The implementation team consisted of four lecturers from the Department of Mathematics, Faculty of Mathematics and Natural Sciences, Sriwijaya University, and eight students. The results of the test demonstrated that 92.8% of participants scored above 80, and 85.7% of participants indicated that they strongly agreed that this mentoring activity was beneficial and hoped that it could be continued